Nanotechnology in neurosurgery: thinking small, dreaming big. (3rd September 2017) - Tan, Aaron; Jeyaraj, Rebecca; Ashkan, Keyoumars
Abstract: Nanotechnology has the power to transform neurosurgery by facilitating intervention at the cellular and subcellular level. The unique properties of nanomaterials will not only improve the management of conditions traditionally treated through neurosurgery, but also make neurosurgical intervention possible for diseases where there are currently limited treatment options. Specifically, nanotechnology appears to be a promising tool for improving molecular imaging, seamlessly integrating diagnosis and therapy in neuro-oncology, identifying targets for selective neuromodulation, as well as promoting neuroregeneration. Despite the vast potential benefits of nanotechnology in neurosurgery, problems related to neurotoxicity and the long-term medical and social consequences must be adequately addressed before nanotechnology becomes a component of surgical care.